Status Kerentanan Larva Aedes aegypti terhadap Temefos (Organofosfat) di Tiga Kabupaten/Kota Provinsi Aceh - Mara Ipa; Joni Hendri; Lukman Hakim; Rizky Muhammad (Loka Litbang Kesehatan Pangandaran, 2017)
Dengue haemorrhagic fever (DHF) incidence rate in Aceh Province for the past three years 2012-2014 were fluctuated from 51‰, 29‰ and 45‰. The most widely used larvacide to control larvae Ae. aegypti is temefos, in Indonesia 1% temefos (abate 1SG) started used in 1976, and since 1980 has been used for the eradication program of Ae. aegypti larvae. The intensive use of temefos will not be a problem until population was dominated by resistant individuals. The purpose of this study was to determine the status of susceptibility of Ae. aegypti larvae against temefos in three dengue fever endemic areas in Aceh. We conducted an observational study to examine the susceptibility of Ae. aegypti population in 3 districts of Aceh Province: Banda Aceh, Lhokseumawe and Aceh Besar. Entomological survey and larval collection was assigned. Larvae then reared in laboratory until third generation. Third and early fourth instars stage of Ae. aegypti larvae were used as test samples. Susceptibility test was undergo based on World Health Organization guidelines. Results show that larva Ae. aegypti from Banda Aceh (100%) and Lhokseumawe (99%) districts was still susceptible, while Aceh Besar (97%) indicates tolerance to temefos 0,02%. In conclusion, temefos still effective to be used as larvicide for vector control in those three endemic of dengue fever in Aceh Province. The priority vector control program that can be suggested is put mosquito breeding place eradication called PSN as a proactive movement in community.